The relationship between teachers' cue-utilization and their monitoring accuracy of students' text comprehension. (August 2021) - van de Pol, Janneke; van Gog, Tamara; Thiede, Keith
Abstract: We investigated to what extent teachers' use of diagnostic cues and the accuracy with which they interpreted or judged the values of those cues affected teachers' monitoring accuracy. Forty-six secondary education teachers judged the text comprehension of six students (216 students in total). Mere use of diagnostic cues appeared not sufficient. Rather, accurately judging the values of a diagnostic performance cue was related to higher monitoring accuracy. Using non-diagnostic student cues hampered teachers' monitoring accuracy. The key to further improve monitoring accuracy might lie in improving teachers' ability to accurately judge diagnostic cues and help them ignore non-diagnostic cues. Highlights: Teachers' monitoring accuracy of their students' text comprehension was investigated. Performance cues, student cues, and task cues were available during monitoring. Mere use of diagnostic cues was not sufficient to promote teachers' monitoring accuracy. Using non-diagnostic student cues (e.g., students' extraversion) hampered teachers' monitoring accuracy. Accurately judging the values of one of the diagnostic cues increased teachers' monitoring accuracy.